2000
DOI: 10.1149/1.1393167
|View full text |Cite
|
Sign up to set email alerts
|

Pit Growth Study in Al Alloys by the Foil Penetration Technique

Abstract: The foil penetration technique was used to study pit growth in AA1100-O and AA2024-T3. Preliminary work on AA1100-O foils of different thicknesses indicated that the pit growth rate increased with increasing applied potential, suggesting that pit growth was not under transport control. Foil penetration experiments were also carried out on AA2024-T3 foils of a given thickness, at open circuit as well as anodic potentials. Dichromate ions and other oxidizing agents were added to some test solutions. Dichromate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 7 publications
1
42
1
Order By: Relevance
“…These observations are in stark contrast to the considerable effects that chromates can have at low concentration during exposure at open circuit. Other evidence has indicated that chromates act as cathodic inhibitors, which would not be seen under potentiostatically controlled conditions [14]. …”
Section: Resultsmentioning
confidence: 99%
“…These observations are in stark contrast to the considerable effects that chromates can have at low concentration during exposure at open circuit. Other evidence has indicated that chromates act as cathodic inhibitors, which would not be seen under potentiostatically controlled conditions [14]. …”
Section: Resultsmentioning
confidence: 99%
“…The sample was backed with a piece of filter paper and a Cu foil. Penetration was sensed by monitoring the resistance between the sample and the Cu foil using a detection circuit described previously [11]. A Pt counter electrode and saturated calomel reference electrode (SCE) were used in the foil penetration cell.…”
Section: Methodsmentioning
confidence: 99%
“…The nominal growth rate in the short transverse direction was slower because of the longer path length around grains in that direction. The intergranular nature of the attack was supported by X-ray microfocal radiography analysis of penetrated foils [11].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations